Learning alliance (LA) writeshop - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
15 participants were guided in developing a business case write-ups of data collected from participatory trials of IRRI Superbags as well as business plan for adopting improved storage and drying technologies. The farmers were assisted in using tools that quantify financial benefits to their own enterprise to aid their decisions on whether to adopt technologies.